Joxemiel Bidador (1970-2010): basque culture’s historian in Navarre - Jimeno Aranguren, Roldán (Huarte de San Juan. Geografía e Historia, 2010)
We analyze Joxemiel Bidador’s (1970- 2010) intellectual lifework, particularly, we focus on his contribution to basque culture’s history in Navarre. As linguist, historian and folklorist, he left a huge work about typical basque dances which he studied since the prohibitions after the Council of Trent until XX century. His greatest works were about basque language’s history with an approach from navarrese’s literature history and pamplonese journalism of the three first decades of XX century. Besides, he was the first who criticized openly the historicist idea that tries rebuild contemporaneous basque identity with Navarre’s kingdom medieval politic history.
Keywords: Joxemiel Bidador; Historiography; Navarre; Cultural history; Folklore; Typical dances; Basque literature